New omic and network paradigms for deep understanding of therapeutic mechanisms for Fangji of traditional Chinese medicine - Duan Dayue Darrel; Wang Zhong; Wang Yong-yan (Acta Pharmacologica Sinica, 2018)
Combination therapy with multi-drug regimen as an integrated intervention of several pharmacological compounds that interact with multiple targets, rather than monotherapy using a single compound that targets at a single molecule, is a common strategy for combating complex disease in both Western and traditional Chinese medicine (TCM)[1-3].